2014
DOI: 10.1002/cbf.3033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of proteins showing differential changes during ATP oscillations in chondrogenesis

Abstract: Prechondrogenic condensation is a critical step for skeletal pattern formation. Our previous study showed that ATP oscillations play an essential role in prechondrogenic condensation because they induce oscillatory secretion. However, the molecular mechanisms that underlie ATP oscillations remain poorly understood. We examined how differential changes in proteins are implicated in ATP oscillations during chondrogenesis by using liquid chromatography/mass spectrometry. Our analysis showed that a number of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our previous results demonstrated that ATP oscillations driven by chondrogenic growth factors such as TGF beta and insulin play essential roles for prechondrogenic condensation that is the initial step of chondrogenesis by inducing oscillatory expression of proteins involved in actin dynamics, cell migration, and adhesion which leads to collective migration and adhesion3856. The present results demonstrate that ES generates Ca 2+ /ATP oscillations in MSCs even in the absence of exogenous growth factors (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Our previous results demonstrated that ATP oscillations driven by chondrogenic growth factors such as TGF beta and insulin play essential roles for prechondrogenic condensation that is the initial step of chondrogenesis by inducing oscillatory expression of proteins involved in actin dynamics, cell migration, and adhesion which leads to collective migration and adhesion3856. The present results demonstrate that ES generates Ca 2+ /ATP oscillations in MSCs even in the absence of exogenous growth factors (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…The supernatants were concentrated and desalted using the Amicon Ultra Centrifugal Filters (3,000 MWCO, EMD Millipore, Darmstadt, Germany). Nano liquid chromatography–mass spectrometry (LC–MS) was performed as described previously (Kwon, Kurono, Kaneko, Ohmiya, & Yasuda, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…(3,000 MWCO, EMD Millipore, Darmstadt, Germany). Nano liquid chromatography-mass spectrometry (LC-MS) was performed as described previously (Kwon, Kurono, Kaneko, Ohmiya, & Yasuda, 2014).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%